Exploring Novel Silyl-Phosphonite Chemistry and New Bioisosteres - Wheeler, D F (2020)
Phosphinic acids are valuable synthetic targets which have many industrial applications. Most notably they have displayed biological activity as herbicides, and as pharmaceutical drugs for the treatment of a range of diseases. Herein, we report a novel P-C bond formation reaction for the synthesis of secondary phosphinic acids. This method is underpinned by the generation of a nucleophilic silylphosphonite intermediate via an unprecedented B(C6F5)3-catalysed silylation of primary phosphinic acids. A proposed mechanism for this transformation has been reported, and the scope of the reaction has been explored, with 20 secondary phosphinic acids being synthesised in 44 - 96% yield. Furthermore, the functionalisation of these phosphinic acids has allowed the synthesis of 8 Pstereogenic tertiary phosphine oxides. The outlined strategy constitutes a controlled route to tertiary phosphine oxides, which avoids PCl3 and other halophosphines.